Higher education in India : in search of equality, quality and quantity - Tilak, Jandhyala B. G. (India Orient Black Swan, 2018)
Contributed articles.
section I. Democracy, equality and universality -- section II. Equality to inclusion in higher education -- section III. Excellence in higher education -- section IV. Case studies on higher education -- section V. Public expenditure on education -- section VI. State, markets and globalisation -- section VII. Towards reforming higher education.
"EPW, Tata Institute of Social Sciences."
"Essays from Economic and political weekly"--Cover.
Includes bibliographical references.
Keywords: Education, Higher -- India